The Concept Of Property And Welfare Through Abu Ubaid - Muchtar, Evan Hamzah; Supriadi, Supriadi; Rahmawati, Destiani (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
This research discusses wealth and welfare through the thought of Abu Ubaid, who is known as the Amwal and Al-Kharaj books. The problem of this research is related to taxes and zakat which are managed by the state which are not in accordance with their designation, in the sense that the current tax is burdened more on Muslims than on importers or non-Muslims. The purpose of this research is that the thoughts of Abu Ubaid regarding wealth and welfare can be an inspiration for our country in managing taxes and zakat. The research method used in this research is using qualitative research, descriptive analytical, the data used in this research is secondary data from previous studies. The results of this research show that the concept of wealth and welfare of Abu Ubaid's  is good and very relevant to be applied in Indonesia.